PENYEBAB KEJADIAN PADA IBU DENGAN KELAHIRAN BAYI PREMATUR RSUD CENDRAWASIH DOBO (MALUKU) - Hasan Kadatua, Marwa; Wakano, Melawati; Nanlohy, Wildia; Yana Sojem, Maria (Midwifery And Complementary Care, 2025)
Background:  Data from the World Health Organization (WHO) in 2020 estimated that there were 13.4 million premature babies, in 2021 Indonesia was ranked 5th with the highest number of premature births, which was around 657,700, more than 1 in 10 babies. The increase in premature births continues to occur until 2022, which is around 15 million premature babies. Meanwhile, Cendrawasih Dobo Hospital (Maluku) in the Perinatology Room in 2022 recorded 5 premature babies, in 2023 there were 10 babies and in 2024 from January to August as many as 15 premature babies were born. Objective:. The aim of this research is to find out the causes of premature births. Methods: This qualitative study employed a phenomenological design. Data were obtained through in-depth interviews with 10 participants, consisting of both primary and key informants. The data collection methods included semi-structured interviews, audio recordings, documentation, and field notes. Result: There are several causes of premature births that occurred in informants, namely the mother's age being too young, less than 20 years old when experiencing pregnancy, trauma during pregnancy (falling), multiple pregnancies, hypertension during pregnancy and work that is too heavy. Keywords: Delivery, Premature Babies